Characterization of aging-associated cardiac diastolic dysfunction. - Wei-Ting Chang (Public Library of Science (PLoS), 2014)
Aims Diastolic dysfunction is common in geriatric heart failure. A reliable parameter to predict myocardium stiffness and relaxation under similar end-diastolic pressure is being developed. We propose a material and mathematical model for calculating myocardium stiffness based on the concept of linear correlation between [Formula: see text] and wedge pressure. Methods and results We enrolled 919 patients (male: [Formula: see text][Formula: see text]). Compared with the younger population of controls (mean age: [Formula: see text] years; [Formula: see text]; male: [Formula: see text] [Formula: see text]), the elderly (mean age: [Formula: see text]; [Formula: see text]; male: [Formula: see text] [Formula: see text]) had a greater prevalence of hypertension, diabetes mellitus, and coronary artery disease (all [Formula: see text]). We collected their M-mode and 2-D echocardiographic volumetric parameters, intraventricular filling pressure, and speckle tracking images to establish a mathematical model. The feasibility of this model was validated. The average early diastolic velocity of the mitral annulus assessed using tissue Doppler imaging was significantly attenuated in the elderly ([Formula: see text]: [Formula: see text] vs. [Formula: see text]; [Formula: see text]) and corresponded to the higher estimated wedge ([Formula: see text]) pressure ([Formula: see text] vs. [Formula: see text]; [Formula: see text]) in that cohort. E (Young's modulus) was calculated to describe the tensile elasticity of the myocardium. With the same intraventricular filling pressure, E was significantly higher in the elderly, especially those with [Formula: see text] values [Formula: see text]. Compared with diastolic dysfunction parameters, E also presented sentinel characteristics more sensitive for detecting early myocardial relaxation impairment, which indicates stiffer myocardium in aging hearts. Conclusion Our material and geometric mathematical model successfully described the stiffer myocardium in aging hearts with higher intraventricular pressure. Additional studies that compare individual differences, especially in health status, are needed to validate its application for detecting diastolic heart failure.